NUMERIC RATING SCALE ANALYSIS OF TRIGEMINAL NEURALGIA PATIENTS BEFORE AND AFTER MICROVASCULAR DECOMPRESSION - Elena Ghentilis Fitri Amelia, -
Abstract Background: Trigeminal Neuralgia is a common condition of facial pain and its significantly affect patientsâ€™ daily life. Microvascular decompression is one of the interventional pain management for trigeminal neuralgia. There is still a little data obtained on evaluation of facial pain after microvascular decompression in Indonesia. Â Â